FITUR PODCAST PADA SPOTIFY SEBAGAI MEDIA KOMUNIKASI HINDU DI ERA SOCIETY 5.0 - dewa_permana21, I Dewa Gede Darma Permana; Ayu Candra, Widya (UHN IGB Sugriwa Denpasar, 2025)
The Podcast feature application on Spotify in the Society 5.0 era shows a relatively high level of utilization. This high level reflects human adaptation to technological developments that are tailored to needs in various aspects of life. Therefore, the Podcast feature on Spotify can be used positively as a medium for Hindu communication in the Society 5.0 era. The spread of Hindu religious teachings through communication media is something that needs to be taken into account at this time. This is because along with technological developments, religious values ​​experience the potential for degradation. Based on these circumstances, researchers are interested in comprehensively studying the use of the Podcast feature on Spotify as a medium for Hindu communication in the Society 5.0 era. This research uses a qualitative type of research based on a visual ethnographic approach. This research originates from primary data from literature studies and is strengthened by field data using three types of methods, namely reflective, collaborative and participatory. This research shows that the use of the Podcast feature on Spotify as a medium for Hindu communication in the Society 5.0 era has the advantage of producing Podcasts that are more contemporary, creative, innovative and more attractive. Not only as a communication medium, the Podcast feature on Spotify is also a medium for education, inspiration and entertainment. Based on this, the Podcast feature on Spotify can be said to be an effective platform as a medium for Hindu communication in the Society 5.0 era.